Doctor of Physical Therapy Education in a Hybrid Learning Environment: Reimagining the Possibilities and Navigating a "New Normal". Issue 8 (18th May 2020) - Gagnon, Kendra; Young, Brian; Bachman, Teresa; Longbottom, Thomas; Severin, Richard; Walker, Michael J
Abstract: Professional physical therapist education has experienced a transformation over the last few decades, moving to a doctoring profession with more autonomy and a broader scope of practice. These changes have occurred in parallel with systemic and structural changes in health care and higher education, both of which have experienced challenges with improving access and controlling costs, and have become a centerpiece of legislative and political discourse. At the same time, advances in technology have introduced new possibilities in education, with the emergence of online, blended, and "flipped" learning models that supplement or replace face-to-face instruction with distance learning. Hybrid education is a type of blended learning, utilizing both face-to-face and online instructional strategies. In a hybrid learning environment, online content may be delivered synchronously or asynchronously, replacing traditional face-to-face instructional time and reducing "seat time" for students. Recent attention has been brought to online and hybrid/blended learning in physical therapist education in the wake of the COVID-19 pandemic, as programs have been required to abruptly move from face-to-face to remote instruction. Hybrid and other forms of blended learning strategies have been described at the physical therapist education course level. However, there is no literature describing hybrid learning implementation at the physical therapist education program "levels, " and there has been limited discussion on best practices for delivering hybrid, blended, and online instruction in physical therapist education. This perspective provides an overview of hybrid education, describes theoretical frameworks that guide implementation of a hybrid education curriculum, and discusses future directions for hybrid physical therapist education and educational research.